Characters Feature Extraction Based on Neat Oracle Bone Rubbings - Lei Guo (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
In order to recognize characters on the neat oracle bone rubbings, a new mesh point feature extraction algorithm was put forward in this paper by researching and improving of the existing coarse mesh feature extraction algorithm and the point feature extraction algorithm. Some improvements of this algorithm were as followings: point feature was introduced into the coarse mesh feature, the absolute address was converted to relative address, and point features have been changed grid and position relationship integrating into the feature vector. The recognition effect has been improved greatly using this algorithm to recognize oracle characters on the neat bone rubbings. At the same time, it could supply some help to recognize words of the neat handwriting instruments. DOI: http://dx.doi.org/10.11591/telkomnika.v11i9.3302